Emotion-Focused Coping of Former Drug-User Addiction Counselors in Dealing with Work Stress from the Perspective of Character Education - Firdaus Irwansyah; Hery Wibowo; Risna Resnawaty (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
Addiction counselors with a history of drug abuse recovery hold a unique position because they assist clients in the rehabilitation process while also maintaining their own recovery. This study aims to examine the emotion-focused coping strategies used by former drug-user addiction counselors in dealing with work stress from the perspective of character education. This research used a qualitative approach with a case study design at Yayasan Sekar Mawar, West Bandung Regency, West Java. Data were collected through in-depth interviews, observation, and documentation study. The main informants consisted of three addiction counselors with a history of drug abuse, while two supporting informants were involved to provide an institutional perspective. The findings show that addiction counselors experience work stress from various sources, including diverse client characteristics, family pressure, demands to be role models, monotonous work routines, and personal vulnerability in maintaining recovery. The dominant coping strategy used by the counselors is emotion-focused coping, particularly positive reappraisal, self-controlling, and distancing. From the perspective of Thomas Lickona’s character education, these coping strategies reflect the formation of moral knowing through self-awareness and understanding of personal limits, moral feeling through emotional control and empathy, and moral action through the counselors’ consistency in professionally assisting clients. This study concludes that emotion regulation among addiction counselors functions not only as a strategy for managing work stress but also as a process of character formation, including self-control, responsibility, reflection, and resilience in maintaining recovery.